An e-Ambulance Project in Kochi Prefecture, one rural area in Japan - Yoshihisa Matsumoto; Masaru Ogawa; Masatsugu Tsuji (International Telecommunications Society (ITS), 2017)
This study aims at evaluating the economic effect of a e-ambulance project, or emergency telemedicine in the rural areas in Kochi Prefecture in Japan. The focus is on ambulances equipped with ICT devices which transmit images of acute patients to remote hospitals. Kochi Prefecture started the e-ambulance project in Aki and Muroto Cities in 2012. From two cities, it takes approximately one hour to reach emergency hospitals located in Kochi City, the prefectural capital. One of the merits of e-ambulance with the image transmitting system is that doctors in accepting hospitals can monitor real time situation of a patient and prepare for necessary treatment prior to the time patient arrives. They thus save time and effort. In measuring benefit, this study employs different methodology; the e-ambulance project enhances wellness of residents since they perceive more secure. Thus the contingent valuation method (CVM) is applied and willingness to pay (WTP) is used as an index of benefit and estimated based on surveys to residents, which amounts to 1,747 yen per resident per year. Total cost calculated is 381,792,228 yen over three years, and accordingly, B/C ratio amounts 0.459.
Keywords: 330; e-ambulance; WTP; Cost-benefit analysis; CVM; B/C ratio